Identificación de Patologías en Ovarios de Camélidos en los Camales - Pino Panchi, Lenin Michael (2018)
This research is carried out with the taking of samples of ovaries, at Rastro Quito slaughterhouse with a total of 16 Lama glama female, having as objective to identify of ovaries in South American camelids, and thus obtaining the prevalence, and morphometric of the same and stablishing the total number of animals slaughtered in the different slaughterhouse. To development of practice collected 32 samples of ovaries, subsequently moving them into Petri box with saline for conversation, in the biotechnology laboratory of the Universidad Técnica de Cotopaxi, come from the measurement of the ovaries in long, width and thickness; developing tables with the respective measures and ranks, as a result can identify, mention and classify the pathologies that there are in the left and right ovary, characterizing the measures outside normal ranges. Of the 32 samples identify 1 ovarian follicular cyst that shows 3.5 cm long, 2.5 cm wide and 2 thick, which has a prevalence of 3.1 and 3 ovaries with ovarian hypoplasia, with less measures to normal ranger 0.3 cm long, 0.3 cm wide, 0.1 cmi thickness with a prevalence by illness of 9.4% and eventually with a prevalence of 6.25% of the total of ovarian pathologies.